Can CCRT/RT Achieve Favorable Oncologic Outcome in Rectal Cancer Patients With High Risk Feature After Local Excision? - Kim, Seijong; Huh, Jung Wook; Lee, Woo Yong; Yun, Seong Hyeon; Kim, Hee Cheol; Cho, Yong Beom; Park, Yoon Ah; Shin, Jung Kyong (Frontiers in Oncology, 2022)
Purpose: The oncologic outcome of concurrent chemoradiotherapy (CCRT) after local excision in patients with high-risk early rectal cancer as compared with radical operation has not been reported. The aim of this study is to compare the oncologic outcome between radical operation and adjuvant CCRT after local excision for high-risk early rectal cancer. Materials and Methods: From January 2005 to December 2015, 266 patients diagnosed with early rectal cancer and treated with local excision who showed high-risk characteristics were retrospectively analyzed. Propensity score matching was applied in a ratio of 1:4, comparing the CCRT/radiotherapy (RT) (n = 34) and radical operation (n = 91) groups. Univariate and multivariate analyses were performed to identify prognostic factors for survival. Results: The median follow-up period was 112 months. The 5-year disease-free survival rate and the 5-year overall survival of the radical operation group were significantly higher than those of the CCRT/RT group after propensity score matching (96.7% vs. 70.6%, p < 0.001; 100% vs. 91.2%, p = 0.005, respectively). In a multivariate analysis, salvage therapy type and preoperative carcinoembryonic antigen (CEA) were prognostic factors for 5-year disease-free survival (p < 0.001 and p = 0.021, respectively). The type of salvage therapy, the preoperative CEA, and the pT were prognostic factors for 5-year overall survival (p = 0.009, p = 0.024, and p = 0.046, respectively). Conclusions: Patients who undergo radical operation after local excision with a high-risk early rectal cancer had better survival than those treated with adjuvant CCRT/RT. Therefore, radical surgery may be recommended to high-risk early rectal cancer patients who have undergone local excision for more favorable oncologic outcomes.